Associations between internal and external training load measures and neuromuscular performance in elite soccer players - Collins, J. J.; Malone, S.; Collins, K. D. (Sport Sciences for Health, 2025)
The study investigates the relationship between internal and external training load and neuromuscular performance in elite soccer players. Twenty-eight professional players from a squad across a season participated. Players performed a countermovement jump as a measure of neuromuscular performance, with tests conducted the day before a game. Training load data were aggregated over 7-, 14-, and 28-day periods to assess their relationship with performance metrics, including reactive strength index modified (RSI-mod), time to take off, and jump height. Internal load was measured using session ratings of perceived exertion, while external load was analyzed with 10 Hz GPS units. External load measures included total distance, high-speed running, sprint distance, and accelerations and decelerations. In the 7-day window, total distance (ES = 0.03) and acceleration (ES = 0.04) showed a weak positive relationship with performance metrics. In the 14-day window, RSI-mod and time to take off significantly interacted with internal load (ES = 1.54) and high-speed running (ES = 1.44). For the 28-day window, jump height was strongly associated with sprint distance (ES = 1.86). Practitioners should use a multi-metric approach with measures of NMP and should evaluate both outcome and strategy metrics within a force-time curve, to gain a deeper understanding of their athletes.